Evaluation of inhalation technique of community pharmacists - focus on dry powder inhalers - Jovanović, Marija; Roganović, Maša; Kovačević, Milena; Ćulafić, Milica; Vučićević, Katarina; Vezmar Kovačević, Sandra; Milenković, Branislava; Miljković, Branislava (Archives of Pharmacy, 2022)
Treatment of asthma and chronic obstructive pulmonary disease (COPD) requires optimal use of inhalers. Pharmacists have a significant role in educating patients on the correct use of inhalers, including dry powder inhalers (DPI). The aim of the study was to assess and compare pharmacists’ DPI technique demonstration skills before and after the education. The study included only pharmacists without previous training for correct use of inhalers. Pharmacists’ score was assessed at baseline and after the training of the correct use of 5 types of DPI. The participants were given a 1-point score for each of four steps performed correctly. Statistical analysis was performed using the SPSS program (version 25). Wilcoxon test was used for score comparison before and after education. The mean score after training was 3.8±0.57 for all types of DPI. There was a statistically significant difference (p